(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective (s): The objective was to explore frequency of menopause related symptoms among middle aged women and their perception about menopause, Materials and Methods: This was a cross sectional study carried during March to May 2013 among women aged 45-60 years at the out patient Department of Obstetrics and Gynaecology of a tertiary hospital using structured questionnaire. Information was sought regarding menstrual pattern, self reported menopausal symptoms and attitude towards menopausal transition. Data analysis was done using SPSS version 16. Results: Total 106 women were interviewed, The mean age of the respondents was 50.3± 53 years, and 58.5% were post menopausal and 41.5% in menopausal transition. More than half (59.4%) were illiterate, 32% were working. Common menopausal symptoms were insomnia 51.8%, body ache 44.3% and feeling sad 31.3%. Hot flush and night sweats were reported by 50% and 33% respectively. Half of them regard menopause as normal and health seeking for menopausal problems was 42.5%. Conclusion: A significant proportion of women were suffering from vasomotor and psychosomatic symptoms but most of them did not seek treatment. To ensure quality of life health needs of middle aged women should be identified and their views towards menopause incorporated in formulating services for them Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 10-15